Does Nitrofurantoin Improve the Portfolio of Vets against Resistant Bacteria in Companion Animals? - Cristina Vercelli; Michela Amadori; Graziana Gambino; Giovanni Re (MDPI AG, 2023)
In clinical practice in dogs and cats, antimicrobials are frequently used, sometimes overused or misused, increasing antimicrobial resistance (AMR). In order to limit the phenomenon, laws have been enacted and guidelines for prudent and rational use of antibiotics have been developed. Interestingly, old molecules such as nitrofurantoin could be used to achieve therapeutic success and overcome AMR. To better understand the suitability of this molecule in veterinary medicine, the authors performed a revision of the literature, searching on PubMed and entering the following keywords: nitrofurantoin, veterinary medicine, dog, and cat connected by the Boolean operator "and", without restrictions on the date of publication. Thirty papers were finally selected. It is possible to appreciate that papers dealing with nitrofurantoin have been written from the early 1960s to the middle of the 1970s, and then a long period passed without publications. Only at the beginning of the new century, nitrofurantoin was included or was sometimes the focus of papers dealing with its efficacy in veterinary medicine, mainly in the treatment of urinary tract infections. One recent paper dealt with pharmacokinetic features, and none was dedicated to pharmacokinetic/pharmacodynamic integration or modeling. Nitrofurantoin appears to be still effective against several pathogens that rarely develop resistance to this molecule.